Analisis Dampak Sistem Antrian Digital Berbasis Queuing Theory dalam Meningkatkan Jumlah Nasabah pada Bank Syariah Indonesia (Studi Kasus: Bank Syariah Indonesia KCP Painan) - Husniyah Khairaty; Andis Febrian (Lembaga Yasin AlSys, 2026)
Although the implementation of digital queuing systems in the banking sector has been widely studied as an effort to improve service quality, research specifically analyzing the impact of Queuing Theory-based digital queuing systems on increasing the number of customers in Islamic banking, particularly at Bank Syariah Indonesia (BSI) KCP Painan, remains limited. This study aims to analyze the impact of implementing a Queuing Theory-based digital queuing system in supporting an increase in the number of customers at BSI KCP Painan. This study employed a qualitative approach with a case study design. Informants were selected through purposive sampling and included the branch manager, customer service officers, tellers, security officers, and customers. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results showed that the implementation of the digital queuing system created more orderly, transparent, and systematic services through the management of customer arrival sources, arrival patterns, service mechanisms, queuing discipline, and system capacity. However, the effectiveness of its implementation was still influenced by fluctuations in the number of customer arrivals, limited service capacity, office location, and the extent of digital service dissemination to the public. These findings confirm the relevance of Queuing Theory to Islamic banking service management and indicate that optimizing the digital queuing system needs to be supported by adequate service capacity and customer digital literacy. This study provides practical implications for BSI in optimizing service capacity, expanding the dissemination of digital services, and developing service strategies that are more adaptive to customer needs. Future research is recommended to expand the research locations and combine qualitative and quantitative approaches to obtain more comprehensive findings.